Exercise end-tidal carbon dioxide pressure: a new prognostic marker after acute myocardial infarction?. (11th May 2021) - Ferreira, J; Rio, P; Castelo, A; Cardoso, I; Silva, S; Ferreira, RC
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Although several cardiopulmonary exercise testing (CPET) parameters have already proved to predict prognosis, there is increasing interest in finding variables that do not require maximal effort. End-tidal carbon dioxide pressure (PETCO2), an indirect indicator of cardiac output, is one of such variables. Studies in heart failure populations already suggest its role as a prognostic factor. However, data concerning other populations are still scarce. Purpose: To assess the association between exercise PETCO2, cardiac biomarkers and systolic function following acute myocardial infarction (AMI) and to evaluate its potential prognostic role in this population. Methods: A retrospective single-centre analysis was conducted including patients who underwent symptom-limited CPET early after AMI. We assessed PETCO2 at baseline (PETCO2-B), at anaerobic threshold (PETCO2-AT) and at peak exercise and calculated the difference between PETCO2-AT and PETCO2-B (PETCO2-difference). We analysed their association with B-natriuretic peptide (BNP), maximal troponin after AMI as well as with left ventricular ejection fraction (LVEF) 1 year after. Results: We included 40 patients with a mean age of 56 years (87.5% male), assessed with CPET a median of 3 months after AMI (80% of which were ST-elevation myocardial infarctions). Average respiratory exchange ratio was 1, 1 with 48% of patients not reaching maximal effort. Mean PETCO2-AT was 37mmHg, with a mean increase from baseline of 6mmHg (PETCO2-difference). There was a significant positive correlation between all the PETCO2 variables measured and BNP values at time of AMI and on follow-up (best correlation for PETCO2-AT with BNP at AMI hospitalization, r = 0.608, p < 0.001). Maximal troponin was not correlated with PETCO2. Both PETCO2-AT and PETCO2-difference were significantly and positively correlated with LVEF 1-year post-AMI (r = 0.421, p = 0.040 and r = 0.511, p = 0.011, respectively). Conclusion: PETCO2-AT and PETCO2-difference are both correlated with BNP, an established prognostic marker, and with medium-term systolic function after AMI, suggesting their potential prognostic role in this population. Further studies with larger samples are required to confirm the results of this pilot study and assess PETCO2 as a definite predictor of prognosis after AMI.